Jet Shapes of Isolated Photon-Tagged Jets in Pb-Pb and pp Collisions at sNN =5.02 TeV; Physical Review Letters; Vol. 122, iss. 15 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen